Panorama das ações de educação permanente em saúde mediadas pela Telessaúde realizadas no período pré-pandêmico e no período pandêmico da COVID-19 - Cosme, Keven de Oliveira (2024)
This research aimed to describe the EPS actions mediated by Telehealth using the virtual learning platforms of the SUS carried out in the pre-pandemic and pandemic period of COVID- 19 in Brazil, in addition to analyzing the themes of the courses offered and describing their modalities, obtaining the profile, professional category and quantity of users of the platforms. This is a descriptive, quantitative study that used secondary data provided by the UNA-SUS and AVASUS platforms, such as description of the EPS courses, modalities, period of offer, entrants, graduates, sociodemographic profile and profession of registered users and offering institutions. Data between the dates of January 2018 and May 5, 2023, were included. Descriptive analyses were performed and analyzed in the Microsoft Excel Program (2016) by descriptive statistics, expressed in graphs and tables containing absolute or relative frequencies. Approximately 498 different EPS courses were found offered by both platforms, which have different approaches to the courses. In the pre-pandemic period, AVASUS focused on courses on the themes of Primary Health Care and Food and Nutrition. During the pandemic period, its approach changed to offering courses on the themes of COVID-19, Rare Diseases, and Sexually Transmitted Infections. In the first period, UNA-SUS offered many courses on the themes of Primary Health Care and Public Health Management. During the pandemic period, it maintained the largest offering on these themes, but developed other themes such as COVID- 19, Digital Health, Neglected Diseases, Health of the Elderly, and Patients with Special Needs. The sociodemographic profile and profession of users registered on the platforms was more prevalent among young people aged 21 to 30, students, female, white, with a degree in education, and residents of the Southeast region of Brazil. The total number of entrants to the EPS courses on both platforms in the pre-pandemic period is approximately 2,496,829 entrants and in the pandemic period it is approximately 10,447,039 entrants. Most of the course modalities were for professional qualification. The incorporation of technologies, as pedagogical innovation, guaranteed access, autonomy and dissemination of technical-scientific knowledge to health professionals, during the COVID-19 pandemic. From this, qualitative studies should be carried out to know how these EPS courses impacted life and practical applicability in health services after and during the pandemic period.